Neurochemical Alterations in Sudden Unexplained Perinatal Deaths—A Review - Muhammad, Nazeer; Sharif, Muhammad; Amin, Javeria; Mehboob, Riffat; Gilani, Syed Amir; Bibi, Nargis; Javed, Hasnain; Ahmed, Naseer (Frontiers in Pediatrics, 2018)
Sudden unexpected perinatal collapse is a major trauma for the parents of victims. Sudden infant death syndrome (SIDS) is unexpected and mysterious death of an apparently healthy neonate from birth till one year of age without any known causes, even after thorough postmortem investigations. However, the incidence of sudden intrauterine unexplained death syndrome (SIUDS) is seven times higher as compared to SIDS. This observation is approximated forty to eighty percent. Stillbirth is defined as death of a fetus after 20th week of gestation or just before delivery at full term without a known reason. Pakistan has the highest burden of stillbirth in the world. This basis of SIDS, SIUDS and stillbirths eludes specialists. The purpose of this study is to investigate factors behind failure in control of these unexplanined deaths and how research may go ahead with improved prospects. Animal models and physiological data demonstrate that sleep, arousal, and cardiorespiratory malfunctioning are abnormal mechanisms in SIUDS risk factors or in newborn children who subsequently die from SIDS. This review focuses on insights in neuropathology and mechanisms of SIDS and SIUDS in terms of different receptors involved in this major perinatal demise. Several studies conducted in the past decade have confirmed neuropathological and neurochemical anomalies related to serotonin transporter, substance P, and Acetyl choline α7 nicotine receptors etc. in sudden unexplained fetal and infant deaths. There is need to focus more on research in this area to unveil the major curtain to neuroprotection by underlying mechanisms leading to such deaths.